(untitled) (Conversatoria Linguistica, 2019)
More and more experience in working with bilingual children allows the Krakow Method therapists effectively build two language systems in the mind of the bilingual child’s and develop his communicative competence in both languages by the technique of writing and drawing a diary of events. The overriding function of the diary of events is to assist in the acquisition and enrichment of the language.